Ocimum gratissimum Essential Oil and Its Isolated Compounds (Eugenol and Myrcene) Reduce Neuropathic Pain in Mice - Paula-Freire, Lyvia Izaura Gomes; Molska, Graziella Rigueira; Andersen, Monica Levy; Carlini, Elisaldo Luiz de Araújo (Planta Medica, 2016)
Ocimum gratissimum is used in popular medicine to treat painful diseases. The antihypernociceptive properties of O. gratissimum essential oil and two of its active components (eugenol and myrcene) were tested in a model of neuropathic pain induced by a chronic constriction injury of the sciatic nerve. In tests to determine chronic antinociception, adult male C57BL/6 J mice were treated orally with corn oil (control group), O. gratissimum essential oil at doses of 10, 20, or 40 mg/kg or eugenol or myrcene at doses of 1, 5, or 10 mg/kg for 14 days after surgery. Pregabalin (20 mg/kg) was used as a standard in this study. The treatment with 20 and 40 mg/kg of O. gratissimum essential oil and at doses of 5 and 10 mg/kg of the active components were able to promote antihypernociception in both mechanical (von Frey) and thermal (hot plate) tests. The treatment with the essential oil of the plant or eugenol was effective in reducing the levels of interleukin-1β in the sciatic nerve. Our findings demonstrate that O. gratissimum essential oil and its isolated active components possess antihypernociceptive activity in neuropathic pain models.
Keywords: Ocimum gratissimum; Lamiaceae; eugenol; myrcene; neuropathic pain; IL-1beta